2022
DOI: 10.3390/v14122811
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus: An Overview of Virology and Preventative Measures

Abstract: Norovirus (NoV) is an enteric non-enveloped virus which is the leading cause of gastroenteritis across all age groups. It is responsible for around 200,000 deaths annually and outbreaks are common in small communities such as educational and care facilities. 40% of all NoV outbreaks occur in long-term and acute-care facilities, forming the majority of outbreaks. Nosocomial settings set ideal environments for ease of transmission, especially due to the presence of immunocompromised groups. It is estimated to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 117 publications
0
18
0
Order By: Relevance
“…Variant replacement is an important pattern of norovirus to adapt to different immunological environments. 9 Ladder-like phylogenetic relationship of strains indicates a temporal replacement of prevalent variants driven by herd immunity. 40 But this was not observed in the GII.6 VP1 gene, indicating the long-term cocirculation of GII.6 variants in the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variant replacement is an important pattern of norovirus to adapt to different immunological environments. 9 Ladder-like phylogenetic relationship of strains indicates a temporal replacement of prevalent variants driven by herd immunity. 40 But this was not observed in the GII.6 VP1 gene, indicating the long-term cocirculation of GII.6 variants in the population.…”
Section: Discussionmentioning
confidence: 99%
“…MCC tree also confirmed that GII.6 VP1 gene was clustered into three groups. Variant replacement is an important pattern of norovirus to adapt to different immunological environments 9 . Ladder‐like phylogenetic relationship of strains indicates a temporal replacement of prevalent variants driven by herd immunity 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It causes around 685 million cases worldwide each year, of which around 200 million are children under the age of 5, around 200 000 deaths (mainly in underdeveloped countries), and costs worldwide economic losses of around £48 billion per year, making it a global problem. 3,4 For this reason, the development of a vaccine against NoV is now considered a high priority by the World Health Organization. 5 Currently, the NoV GI and GII variants are the most commonly detected genogroups worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Norovirus (NoV) is the main pathogen causing AGE sporadic cases and outbreaks worldwide, causing at least 50% of gastroenteritis outbreaks and a major cause of foodborne illness 2 . It causes around 685 million cases worldwide each year, of which around 200 million are children under the age of 5, around 200 000 deaths (mainly in underdeveloped countries), and costs worldwide economic losses of around £48 billion per year, making it a global problem 3,4 . For this reason, the development of a vaccine against NoV is now considered a high priority by the World Health Organization 5 .…”
Section: Introductionmentioning
confidence: 99%